A novel intensity compensation method to achieve energy independent beam intensity at the patient location for cyclotron based proton therapy facilities. Issue 1 (1st January 2023) - Maradia, Vivek; Meer, David; Weber, Damian C; Lomax, Antony J; Psoroulas, Serena
Abstract: In cyclotron-based proton therapy facilities, an energy selection system is typically used to lower the beam energy from the fixed value provided by the accelerator (250/230 MeV) to the one needed for the treatment (230-70 MeV). Such a system has the drawback of increase beam emittance and introducing an energy-dependent beam current at the patient location, resulting in energy dependent beam intensity ratios of about 10 3 between high and low energies. This complicates treatment delivery and challenges patient safety systems. As such, we propose the use of a dual energy degrader method that can reduce beam intensity for high-energy beams. The first degrader is made of high Z material and the second is made of low Z material and are placed next to each other. For high energies (190-230 MeV), we use only the first degrader to increase beam emittance after the degrader and thus lose intensity in the emittance selection collimators. For intermediate energy beams (110-190 MeV) we use the combination of both degraders, whereas for low energy beams (70-110 MeV), only the second degrader limits the increase in emittance. With this approach, energy-independent beam intensities at the patient location can be achieved, whilst localizing beam losses around the degrader.